Glucocorticoid-Induced Tumour Necrosis Factor Receptor-Related Protein: A Key Marker of Functional Regulatory T Cells - Simona Ronchetti; Erika Ricci; Maria Grazia Petrillo; Luigi Cari; Graziella Migliorati; Giuseppe Nocentini; Carlo Riccardi (Journal of Immunology Research)
Glucocorticoid-induced tumour necrosis factor receptor-related protein (GITR, TNFRSF18, and CD357) is expressed at high levels in activated T cells and regulatory T cells (Tregs). In this review, we present data from mouse and human studies suggesting that GITR is a crucial player in the differentiation of thymic Tregs (tTregs), and expansion of both tTregs and peripheral Tregs (pTregs). The role of GITR in Treg expansion is confirmed by the association of GITR expression with markers of memory T cells. In this context, it is not surprising that GITR appears to be a marker of active Tregs, as suggested by the association of GITR expression with other markers of Treg activation or cytokines with suppressive activity (e.g., IL-10 and TGF-β), the presence of GITR+ cells in tissues where Tregs are active (e.g., solid tumours), or functional studies on Tregs. Furthermore, some Treg subsets including Tr1 cells express either low or no classical Treg markers (e.g., FoxP3 and CD25) and do express GITR. Therefore, when evaluating changes in the number of Tregs in human diseases, GITR expression must be evaluated. Moreover, GITR should be considered as a marker for isolating Tregs.